A signature of circulating microRNAs differentiates takotsubo cardiomyopathy from acute myocardial infarction - Jaguszewski, Milosz; Osipova, Julia; Ghadri, Jelena-Rima; Napp, Lars Christian; Widera, Christian; Franke, Jennifer; Fijalkowski, Marcin; Nowak, Radoslaw; Fijalkowska, Marta; Volkmann, Ingo; Katus, Hugo; Wollert, Kai C.; et al. (European heart journal, 2014)
Takotsubo cardiomyopathy (TTC) remains a potentially life-threatening disease, which is clinically indistinguishable from acute myocardial infarction (MI). Today, no established biomarkers are available for the early diagnosis of TTC and differentiation from MI. MicroRNAs (miRNAs/miRs) emerge as promising sensitive and specific biomarkers for cardiovascular disease. Thus, we sought to identify circulating miRNAs suitable for diagnosis of acute TTC and for distinguishing TTC from acute MI.